2013
DOI: 10.1016/j.addbeh.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Dispelling the myth of “smart drugs”: Cannabis and alcohol use problems predict nonmedical use of prescription stimulants for studying

Abstract: This study tested the hypothesis that college students’ substance use problems would predict increases in skipping classes and declining academic performance, and that nonmedical use of prescription stimulants (NPS) for studying would occur in association with this decline. A cohort of 984 students in the College Life Study at a large public university in the US participated in a longitudinal prospective study. Interviewers assessed NPS; Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
86
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(98 citation statements)
references
References 39 publications
9
86
1
2
Order By: Relevance
“…The findings also tell us that students use prescription stimulants non-medically because they believe they are an effective study aid. This feeds into the myth that prescription stimulants are "smart" drugs, which is contradicted by the empirical evidence that shows a negative relationship between grades and NMUPS (Arria et al, 2013;Ford and Schroeder, 2009;McCabe et al, 2005). Prevention and intervention programs need to deconstruct this myth and let students know that prescription stimulants are not a simple path to better grades.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The findings also tell us that students use prescription stimulants non-medically because they believe they are an effective study aid. This feeds into the myth that prescription stimulants are "smart" drugs, which is contradicted by the empirical evidence that shows a negative relationship between grades and NMUPS (Arria et al, 2013;Ford and Schroeder, 2009;McCabe et al, 2005). Prevention and intervention programs need to deconstruct this myth and let students know that prescription stimulants are not a simple path to better grades.…”
Section: Discussionmentioning
confidence: 84%
“…We included a number of controls which prior research has shown increases risk of NMUPS in our models (Arria et al, 2013;McCabe et al, 2005;Rabiner et al, 2010). The controls included demographic characteristics such as age, gender (1 = male), and race (1 = white).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to understand rates of use and to characterize prototypical users is critical for support providers and regulators as they attempt to implement evidence-based health interventions, particularly for students experiencing problems with CE drug misuse (Arria et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Stud. Alcohol Drugs, 74, 714-719, 2013) T HE NONMEDICAL USE OF PRESCRIPTION stimulants (i.e., taking medications without a doctor's orders) as a cognitive performance enhancer among adolescents and young adults has produced an upsurge of research and public debate over the past several years (Arria et al, 2008a(Arria et al, , 2008b(Arria et al, , 2013Arria and DuPont, 2010;Rabiner et al, 2009;Teter et al, 2005Teter et al, , 2006. Currently, 1.2% of people ages 12-17 years and 3.1% of people ages 18-25 years have nonmedically used stimulants during the past year (Substance Abuse and Mental Health Services Administration, 2012).…”
mentioning
confidence: 99%